Fenomena Maskulinitas Fanboy Boygroup K-Pop Di Kota Denpasar - Prathika Wibowo, Dhea Anisha; Zuryani, Nazrina; Krisna Aditya, I Gst Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT, 2021)
Masculinity is a concept that has always been related to gender, social roles and men. In the phenomenon of masculinity is closely related to life in this modern world, for example the masculinity of K-Pop boygroup fanboys that can give rise to a stigma. The theory used in this study is the theory of deconstruction by Jaques Derrida. This study examined the masculinity of K-Pop boygroup fanboys in Denpasar City which is often questioned and even given stigma. This is because K-Pop music is displayed by prioritizing dance, makeup, physical appearance, and clothing. Furthermore, the image of the Korean music industry mostly provides a cute, girly, and sweet style. In this study also explained how the construction of masculinity understood by society with masculinity created by idol boy group K-Pop and showed the or absence of stigma against the masculinity of K-Pop boygroup fanboys in Denpasar City. Keywords: Masculinity, Stigma, Fanboy K-Pop, Boygroup, Deconstruction